2021
DOI: 10.1136/bmjopen-2020-046098
|View full text |Cite
|
Sign up to set email alerts
|

Prospective cohort study comparing a triceps-sparing and triceps-detaching approach in total elbow arthroplasty: a protocol

Abstract: BackgroundNew surgical approaches have been developed to optimise elbow function after total elbow arthroplasty (TEA). Currently, there is no consensus on the best surgical approach. This study aims to investigate the functional outcomes, prosthetic component position and complication rates after a triceps-sparing and a triceps-detaching approach in TEA.Methods and analysisA multicentre prospective comparative cohort study will be conducted. All patients with an indication for primary TEA will enrol in either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Most recently and reflecting the important of the current work, Meijering et al [15] registered a large trial to establish a consensus on the ideal approach for total elbow arthroplasty [triceps sparing vs. triceps detaching]. They suggested that, no consensus is present on the best surgical approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most recently and reflecting the important of the current work, Meijering et al [15] registered a large trial to establish a consensus on the ideal approach for total elbow arthroplasty [triceps sparing vs. triceps detaching]. They suggested that, no consensus is present on the best surgical approach.…”
Section: Discussionmentioning
confidence: 99%
“…Radiological outcome revealed that, union achieved in all patients. The mean time of bone union was 14.8 ± 0.72 weeks [12][13][14][15][16][17][18][19][20]. There were no non-union.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation